If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -17 = 6x + 7 Reorder the terms: -17 + 12x = 6x + 7 Reorder the terms: -17 + 12x = 7 + 6x Solving -17 + 12x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -17 + 12x + -6x = 7 + 6x + -6x Combine like terms: 12x + -6x = 6x -17 + 6x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -17 + 6x = 7 + 0 -17 + 6x = 7 Add '17' to each side of the equation. -17 + 17 + 6x = 7 + 17 Combine like terms: -17 + 17 = 0 0 + 6x = 7 + 17 6x = 7 + 17 Combine like terms: 7 + 17 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 4*15*6= | | 3(2c-3)-6=4c+9 | | 3u=30-2u | | X-(-10)=15 | | 3x+17=3(x+2)+11 | | x-3/10 | | 5x+3=2x-3+3x | | 7x+6=3x+8 | | 2x-5y=-45 | | -k-8(8k-6)=-16-k | | 1-4i= | | R-15=-12 | | 15500=C+0.30(15500) | | -2(-7W+3)-8W=2(W-5)-6 | | 2(x-7)=8+3x | | -1=k-9 | | x-3/10=4x | | -3c+7=-17 | | 7n+x=3x-n | | 6n+3=-4n+7 | | x²√25/289 | | 12x-3y=-36 | | (6x-4)(4n-5)= | | -78=3j+7-8j | | 25=40+s | | 27x=28 | | 4x^2+14-210=0 | | p-3/8 | | 3x/y=6 | | X+17=151 | | (12-5i)(7i+5)= | | A+2(y+3)=y+7 |